Can Antiretroviral Therapy Modify the Clinical Course of HDV Infection in HIV-Positive Patients?. Issue 7 (October 2015) - Onali, Simona; Figorilli, Francesco; Balestrieri, Cinzia; Serra, Giancarlo; Conti, Maria; Scioscia, Rosetta; Barca, Lucia; Lai, Maria E; Chessa, Luchino
Background: Infection with hepatitis delta virus (HDV) affects approximately 6–14.5% of patients coinfected with HIV-1 and HBV, showing a more aggressive clinical course compared with an HIV-negative population. There is no universally approved treatment for chronic hepatitis D (CHD) in HIV-infected patients. Antiretroviral therapy (ART) containing tenofovir has been recently associated with HDV suppression. Our aim was to evaluate whether the outcome of CHD in HIV-infected patients can be favourably influenced by ART including reverse transcriptase inhibitors. Methods: The clinical course of four HBV/HDV/HIV-coinfected patients receiving ART were retrospectively examined. Results: HDV RNA became undetectable in all patients after a variable period of ART along with the disappearance of hepatitis B surface antigen in two of them, and an increase in CD4 + T-cell count. In all patients, virological changes were associated with improved liver function tests and clinical features. Conclusions: We suggest that ART regimens including drugs active against HBV could have beneficial effects on the clinical course of CHD in patients with HIV-1 by favouring immunological reconstitution.